THE VIEWPOINT OF DIVAN POETS ABOUT BEHRÂM - İsa IŞIK (Fırat University, 2019)
The Divan Literature is a literature, which Turks formed between 13th and 19th centuries, whose effects have continued to the present day and which has Islamic thought in its basis. This literature, which has generally been fed by Islamic culture has been affected by various resources. Among these resources we can primarily mention Islamic facts and figures. The history of prophets and mystical thinking are amongst the sources to affect the Divan poets. Components that are parts of the Turkish history and culture, traditions and customs, the way of life that is led by the common people, local elements and mythological factors are all the building stones of this specific genre of literature. It is of vital importance to know about and be conscious of such references in order to have a better understanding of texts of The Old Turkish Literature. Mythological elements constitute a considerable part of the sources mentioned above and the Persian mythology, with all its heroes and concepts, is an obvious basis. In this respect Firdevsi’s “Şehnâme” is exceptionally crucial. In course of time this book became an inspirational source for Turks just as it had been one for Iranians both historically and culturally. As a consequent the figures and incidents mentioned in Şehnâme were reused and transformed by Divan poets among which we can make mention of Behrâm. In this article, both the usage of the name of Behrâm as a mythological person and the meanings it suggests have been described through quotations from Divan poetry. When samples were made, various